2019
DOI: 10.4103/ajns.ajns_300_18
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube defects: A retrospective study of 69 cases

Abstract: Objective: Neural tube defects (NTDs) are congenital disorders that significantly increase the risk of death and disability in the 1 st year of life. The aim of this study was to retrospectively evaluate the patients admitted to our neonatal intensive care unit because of NTD. Materials and Methods: We retrospectively examined the demographic features, familial risk factors, physical examination and radiological findings, and accompanying dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
(28 reference statements)
0
10
1
Order By: Relevance
“…Neural tube defect (NTD) is a congenital condition in which the vertebral column fails to close and frequently affects the spinal cord. NTD substantially increases the risk of disability and death within the first year of life [1][2][3]. Both genetic and environmental factors are involved in the development of NTD [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Neural tube defect (NTD) is a congenital condition in which the vertebral column fails to close and frequently affects the spinal cord. NTD substantially increases the risk of disability and death within the first year of life [1][2][3]. Both genetic and environmental factors are involved in the development of NTD [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Both genetic and environmental factors are involved in the development of NTD [4,5]. Moreover, its incidence can vary according based on the development status of the country, race, and sex of the child as well as the socioeconomic and education levels of the family [2,[5][6][7]. Different studies have reported the incidence of NTD as 0.72 to 6.2 per 1000 live births [1,2,5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations